Teaching at The Right Level (TaRL) as an Implementation of New Education Concepts in the Insights of Ki Hajar Dewantara - Putri, Helena Anggraeni; Siswanto, Deny Hadi (Indonesian Journal of Educational Science and Technology, 2024)
Education plays an important role in forming a generation that is competitive and superior amidst the complexity of the era of globalization. Ki Hajar Dewantara, who came from a noble lineage from the Yogyakarta Palace, devoted himself to education with full commitment. His philosophical doctrine of National Education reflects his belief that education functions as a pathway that guides individuals towards optimal well-being and happiness in society. According to Dewantara, education functions as a compass for the development of each student, not only depending on the will or authority of the teacher. Currently, the government is formulating a new educational paradigm that features flexibility for educators to adapt classroom teaching, using the Teaching at the Appropriate Level (TaRL) methodology. The correspondence between the characteristics of this new educational framework and Dewantara's educational principles fosters new optimism in the progress of Indonesian education. This study uses a literature review method to assess the resonance between the new educational paradigm and its practical implementation. The findings reveal a harmonious alignment between Ki Hajar Dewantara's philosophical teachings and the application of TaRL within the framework of modern education at the secondary school level. Therefore, integrating TaRL into the educational environment is a real step in realizing Dewantara's vision of building an inclusive and progressive educational landscape.